Decision Support System for Determining Student Representative Management Positions Using Case-Based Reasoning Method - Hervian Jatmika Bimantoro (Institute of Computer Science (IOCS), 2020)
The regeneration of the Sanata Dharma University Student Representative Council (DPMU) management is carried out regularly at the end of each year. One of the stages that DPMU board candidates go through is an interview. The interview aims to assess candidates with the criteria that have been set as DPMU administrators. In the regeneration process, DPMU often finds it difficult to determine positions that match the criteria possessed by the candidate concerned. The problem that will arise when the admissions committee assigns positions to candidates who do not match the criteria they have is that the candidate's performance is not optimal. This decision support system was created to help provide recommendations to the DPMU in determining the position of the position. The system will be made using Case Based Reasoning method. Knowledge data and criteria data used are data owned by DPMU. Testing is done by comparing the results of system calculations with decisions made by the DPMU management manually. From the trial, it was concluded that the system using the Case Based Reasoning method was quite capable in determining the position of the DPMU but not yet satisfactory.